Cure With Interferon‐Free Direct‐Acting Antiviral Is Associated With Increased Survival in Patients With Hepatitis C Virus‐Related Hepatocellular Carcinoma From Both East and West. Issue 6 (8th May 2020) - Dang, Hansen; Yeo, Yee Hui; Yasuda, Satoshi; Huang, Chung‐Feng; Iio, Etsuko; Landis, Charles; Jun, Dae Won; Enomoto, Masaru; Ogawa, Eiichi; Tsai, Pei‐Chien; Le, An; Liu, Matthew; et al.
Abstract : Background and Aims: Survival data among patients with hepatitis C virus (HCV)‐related hepatocellular carcinoma (HCC) after achieving sustained virologic response (SVR) with interferon‐free direct‐acting antivirals (DAAs) in both Asian and western countries are limited. Survival rates were compared between patients with HCV‐related HCC who were untreated for HCV and those who achieved SVR. Approach and Results: Using data from two U.S. and six Asian centers from 2005 to 2017, we categorized 1, 676 patients who were mono‐infected with HCV‐related HCC into patients untreated for HCV (untreated group) and DAA‐treated patients with SVR (SVR group) and matched by propensity score matching (PSM); multivariable Cox regression with HCV treatment status as a time‐varying covariate was used to determine mortality risk and landmark analysis to avoid immortal time bias. There were 1, 239 untreated patients and 437 patients with SVR. After PSM, background risks of the 321 pairs of matched patients were balanced (all P  > 0.05). After time‐varying adjustment for HCV treatment initiation compared with untreated patients, patients with SVR had significantly higher 5‐year overall survival (87.78% vs. 66.05%, P  < 0.001). Multivariable Cox regression showed that SVR was independently associated with a 63% lower risk of 5‐year all‐cause mortality (hazard ratio [HR], 0.37; 95% confidence interval [CI], 0.16‐0.83; P  = 0.016) and 66% lower risk of 5‐year liver‐related mortality (HR, 0.34; 95% CI, 0.13‐0.88; P  = 0.026) with similar trends after removing patients with liver transplants. Landmark analysis at 90, 180, and 360 days showed consistent results (HRs ranged 0.22 to 0.44, all P  < 0.05). Conclusion: In this multinational consortium, patients with HCV‐related HCC who obtained SVR achieved a 60%‐70% improvement in 5‐year survival (both all‐cause and liver related) compared with patients untreated for HCV. Patients eligible for HCC therapy should also be considered for DAA therapy.